Transgressing the Terms of Covenant in the Islamic Jurisprudence of International Relations: The Cases of Socotra and Cyprus in Comparison - Bouzenita, Anke Iman (Intellectual discourse, 2020)
The breaching of treaties between Muslims and Non-Muslims andtheir legal repercussions is an important topic in the Islamic jurisprudence ofinternational relations. This article compares two cases of breach of covenantin Islamic history: Cyprus (1st-2nd century AH) and Socotra (3rd century AH),with regard to the events, their depiction in historical sources, and scholars’legal evaluations of them. These cases reflect different regional backgroundsregarding maritime engagement: the Rightly Guided Caliphate and earlyUmayyad State were reluctant to initiate engagement in the Mediterranean,whereas Oman was a seafaring nation active in the Indian Ocean even beforeIslamic times. The case of Cyprus took place concurrently with the formationof legal schools (madhāhib) and numerous outstanding Sunni scholars wereasked for their verdicts; the case of Socotra was evaluated from an Ibadiviewpoint. Neither case seems to have been discussed in the fiqh compendia ofthe respective other school(s).